Running With a Trot: Editing a Poem in Russian and Kyrgyz by Turusbek Madilbay - Joyce Ellen Turner ([sic])
In fine-tuning Turusbek Madilbay’s rough dictionary translation (a ‘trot’) I became convinced that a good match between writers and editors or translators is essential. I imagine it’s tempting for a writer to throw up her hands, to abdicate responsibility and let the publishing houses use their stock translators, but I recommend that creative writers learn about the process of translation in order to find the best partner for putting their work into another language. The responsibility must never rest solely with the translator, who is always working with limited information and within temporal and fiscal constraints. It’s always, to some degree, piecework. I hope it’s not a breach of publishing protocol to read reviews of work by, and to solicit samples from, several literary translators, and then choose among them. A beginner will do the job more cheaply, but will the skill be there? Do not leave the job to chance. My spotty linguistic background was well-suited to working with a trot. I have never achieved true fluency in a language besides my native English. I have, however, studied academically, at one time or another, French, Ancient Greek and Latin. I have achieved a certain linguistic flexibility from them well as from tourist phrases which I have learned in Spanish, Italian, Greek, Turkish and Arabic. When vocabulary and grammar fail me, I can at least spot word roots and cognates. (I credit Latin teachers’ use of Caesar’s ciphers for my irrational belief that no overheard phrase in a foreign tongue can be as mundane as ‘I think the pickles are on the next aisle’ but instead must be, in significance, on par with an aphorism about crossing the Rubicon.)